Strategic Development of Renewable Energy Sources for Enterprises in the Czech Republic - Hartwich, Michaela; Hönig, Vladimír, 1982-; Procházka, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis examines the economic viability of investing in solar photovoltaic (PV) systems combined with Battery Energy Storage Systems (BESS) within the context of the Czech Republic’s renewable energy transition. The theoretical framework provides an overview of global energy trends, the European Union’s leadership in renewable policies and the energy market of Czech Republic, with a particular focus on the role of solar energy and storage technologies in supporting grid stability and energy decentralization. The practical part develops a technical and financial model for a PV-BESS installation offering flexibility services to the electricity market. Using financial evaluation methods, sensitivity analysis, and Monte Carlo simulations, the thesis assesses the investment’s risk-return profile under different market scenarios. This thesis emphasizes the importance of combining technological innovation with strategic market participation to drive the renewable energy transition, revenues and demonstrates the potential for solar and storage solutions in Czech market.
Vedoucí práce: Vladimír Hönig
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses